Altered Gut Microbiota Taxonomic Compositions of Patients With Sepsis in a Pediatric Intensive Care Unit - Liu, Jing; Wang, Mingbang; Chen, Weiming; Ma, Jian; Peng, Yi; Zhang, Mingzhi; Wang, Chuanqing; Yan, Gangfeng; Lu, Guoping (Frontiers in Pediatrics, 2021)
The gut is thought to play an important role in the pathogenesis of sepsis. Changes in the gut microbiota are closely related to the occurrence and development of human diseases, but few studies have focused on taxonomic composition of gut microbiota in sepsis septic patients. Knowledge of changes in the gut microbiota is a key issue in intensive care. Clinicians must understand how an altered gut microbiota affects the susceptibility and prognosis of sepsis septic patients. Measurements and Main Results: In the Single-center Case control study, Twenty sepsis septic patients and twenty healthy children were recruited. The taxonomic composition of gut microbiota were determined via 16S rRNA gene sequencing. Gut microbiota diversity in children with sepsis was significantly reduced compared with that in healthy children. The taxonomic composition of gut microbiota can effectively distinguish children with sepsis from healthy children. Thirteen taxa of gut microbiota were significantly increased in the guts of children with sepsis compared with those of healthy children. The increased abundances of Enterococcaceae, Enterococcus and Enterococcus durans Enterococcus durans in gut of septic patients were significantly positively correlated with blood inflammation indicators CRP and WBC. The abundances of 7 bacteria were significantly decreased in the guts of septic children compared with those of healthy children. The decreased abundance of Bifidobacteriales in gut of septic patients is significantly negatively correlated with blood inflammation index WBC. Machine learning classifier was built for distinguishing sepsis and achieved the AUC value of 81.25%(,). It shows that the composition of gut microbiota has certain potential for diagnosis of sepsis. Conclusions: Gut microbiota alterations in septic patients exhibit proliferation of opportunistic pathogenic bacteria, the massive reduction of the commensal flora, and the significant decrease in the diversity of the gut microbiota.Dysbiosis may also account for some changes in the inflammation indexes.